Abnormal degree centrality in neurologically asymptomatic patients with end-stage renal disease: A resting-state fMRI study. Issue 1 (January 2016) - Li, Shumei; Ma, Xiaofen; Huang, Ruiwang; Li, Meng; Tian, Junzhang; Wen, Hua; Lin, Chulan; Wang, Tianyue; Zhan, Wenfeng; Fang, Jin; Jiang, Guihua
Highlights: Abnormal intrinsic dysconnectivity pattern of whole-brain functional networks occurs in end-stage renal disease (ESRD) patients using resting-state fMRI. ESRD patients have decreased functional connectivity in the left inferior parietal and left precuneus within the brain network. ESRD patients have increased connectivity in depression-related regions including bilateral inferior frontal gyrus and right superior temporal gyrus. Abstract: Objective: End-stage renal disease (ESRD), characterized by multi-organ dysfunction, has been shown to co-occur with abnormal brain function. Previous resting-state fMRI studies suggested that regional brain spontaneous activity and functional connectivity within the default mode network are abnormal in ESRD patients. The current study aimed to depict intrinsic dysconnectivity pattern of whole-brain functional networks in voxel level in neurologically asymptomatic patients with ESRD. Methods: fMRI datasets were acquired from 22 ESRD patients (without clinical neurological disease) and 29 healthy control (HC) subjects. We investigated the degree centrality for a given element in a network to reveal the changes of functional connectivity throughout the huge human functional network. In the brain regions showing a difference between the HC and ESRD groups, we further conducted receptive operation characteristic (ROC) analyses to confirm the accuracy, sensitivity and specificity of our results. Results: ESRD patients showed decreased functional connectivity in the left inferior parietal and left precuneus within the brain network; both regions are important components of the default-mode network (DMN). In contrast, patients showed increased connectivity in depression-related regions including bilateral inferior frontal gyrus and right superior temporal gyrus. These regions showed an acceptable accuracy (0.68–0.75), sensitivity (0.64–0.70) and high specificity (0.82–0.96) in distinguishing between the two groups. Conclusions: Our findings reveal abnormal intrinsic dysconnectivity pattern of whole-brain functional networks in ESRD patients. Significance: Our results could lead to a better understanding of the intrinsic dysconnectivity patterns of default-mode network-related regions in ESRD patients from the whole brain network perspective.